Estimation of the potential performance in p-type SnSe crystals through evaluating weighted mobility and effective mass - Bingchao Qin; Wenke He; Li-Dong Zhao (Journal of Materiomics, 2020)
It has been proved that the thermoelectric performance of p-type SnSe crystals can be optimized through enhancing carrier concentration. The calculations of electronic band structure elucidate that this approach can be interpreted by including multiple valence bands. To better estimate the potential performance, we proposed the transport properties for p-type SnSe crystals and analyzed the weighted mobility from the experimental results. The weighted mobility approaches ∼600 cm2V−1s−1 when the carrier concentration is as high as ∼6.3 × 1019 cm−3. Combined with obtained lattice thermal conductivity, through rising carrier concentration, the quality factor B possesses significant improvements of ∼235% and 138% at 300 K and 773 K, respectively. Through comparing weighted mobility and Hall mobility, two effective mass values ∼0.9 me and 1.8 me can be derived using carrier concentrations. It is expected that the ZT ∼1.0 at 300K and ZT ∼2.9 at 773 K can be obtained when the carrier concentration of ∼8.0 × 1019 cm−3 and the effective mass ∼1.8 me were selected. This work provides an alternative way to comprehend the performance optimization in thermoelectric community.